Recreational Cannabis Legalization: No Contribution to Rising Prescription Stimulants in the USA - Alexander, Garrett D.; Cavanah, Luke R.; Goldhirsh, Jessica L.; Huey, Leighton Y.; Piper, Brian J. (Pharmacopsychiatry, 2024)
Introduction There have been substantial increases in the use of Schedule II stimulants in the United States. Schedule II stimulants are the gold standard treatment for attention-deficit hyperactivity disorder (ADHD), but also carry the risk of addiction. Since the neurocognitive deficits seen in ADHD resemble those of chronic cannabis use, and the rise in stimulant use is incompletely understood, this study sought to determine if recreational cannabis (RC) legalization increased distribution rates of Schedule II stimulants.Methods The distribution of amphetamine, lisdexamfetamine, and methylphenidate were extracted from the ARCOS database of the Drug Enforcement Administration. The three-year population-corrected slopes of distribution before and after RC sales were evaluated.Results Total stimulant distribution rates were significantly higher in states with RC sales after (p=0.049), but not before (p=0.221), program implementation compared to states without RC. Significant effects of time (p<0.001) and RC sales status (p=0.045) were observed, while time x RC sales status interaction effects were not significant (p=0.406).Discussion RC legalization did not contribute to a more pronounced rise in Schedule II stimulant distribution in states. Future studies could explore the impact of illicit cannabis use on stimulant rates and the impact of cannabis sales on distribution rates of non-stimulant ADHD pharmacotherapies and ADHD diagnoses.
Keywords: marijuana; attention-deficit hyperactivity disorder; amphetamine; lisdexamfetamine; methylphenidate